Following TRACE: The Computer Hobby Movement in Canada - Lungu, Dov; Stachniak, Zbigniew (Scientia Canadensis, 2011)
The subject of this paper is the computer hobby movement in Canada and its role in the introduction and social acceptance of personal computing in this country. The paper offers a case study that focuses on the activities of arguably the earliest Canadian computer hobby organization named the Toronto Region Association of Computer Enthusiasts. The objective of the study is to document and analyze the first decade of the microcomputer hobby movement in Canada and its role in bringing computing into the homes of Canadians.